General Coordinate Formula of Strain (Skew Reflection) of R2 Onto R2 (Global Journal of Science Frontier Research, 2017)
The authors establish a set of presumably new results, which provide general coordinate formula of strain(skew reflection) of ℝ 2 onto ℝ 2 . Several closely related results are also considered.
Keywords: coordinate formula; skew reflection